More Than 12 % Polarization and 20 Minute Lifetime of 15N in a Choline Derivative Utilizing Parahydrogen and a Rhodium Nanocatalyst in Water. Issue 33 (9th July 2018) - McCormick, Jeffrey; Korchak, Sergey; Mamone, Salvatore; Ertas, Yavuz N.; Liu, Zhiyu; Verlinsky, Luke; Wagner, Shawn; Glöggler, Stefan; Bouchard, Louis‐S.
Abstract: Hyperpolarization techniques are key to extending the capabilities of MRI for the investigation of structural, functional and metabolic processes in vivo. Recent heterogeneous catalyst development has produced high polarization in water using parahydrogen with biologically relevant contrast agents. A heterogeneous ligand‐stabilized Rh catalyst is introduced that is capable of achieving 15 N polarization of 12.2±2.7 % by hydrogenation of neurine into a choline derivative. This is the highest 15 N polarization of any parahydrogen method in water to date. Notably, this was performed using a deuterated quaternary amine with an exceptionally long spin‐lattice relaxation time ( T 1 ) of 21.0±0.4 min. These results open the door to the possibility of 15 N in vivo imaging using nontoxic similar model systems because of the biocompatibility of the production media and the stability of the heterogeneous catalyst using parahydrogen‐induced polarization (PHIP) as the hyperpolarization method. Abstract : High polarization in water : By using a heterogeneous nanoparticle catalyst and an efficient pulse sequence, the observation of 15 N nuclear‐spin polarization in excess of 12 % in a choline derivative are demonstrated in water by parahydrogen‐induced polarization (PHIP). A very long T 1 relaxation of over 20 min is also observed, as well as versatility with previous PHIP methods and target nuclei ( 13 C), opening new applications for medical MRI.